Alleviating Barriers Facing Students on the Boundaries of STEM Makerspaces - Madison E. Andrews; Audrey Boklage (MDPI AG, 2024)
Makerspaces have become an increasingly prevalent supplement to K-16 STEM education, and especially so in undergraduate engineering programs. However, they also fall prey to hegemonic, marginalizing norms common in STEM spaces and, ultimately, the modern making movement has remained a white, male, middle-class pursuit. Despite calls to broaden student participation in makerspaces due to the benefits of participation, there has been no examination of why some students choose not to visit these spaces. We surveyed (n = 151) and interviewed (n = 17) undergraduate STEM students to understand the barriers facing students before and during their initial participation. Using the lens of Social Boundary Spaces, we identified six barriers to successfully crossing the boundary into the makerspace, including: (1) not having enough time, (2) not feeling you have a purpose for visiting, and (3) not knowing how to obtain the proper certifications. Further, students find approaching makerspaces to be intimidating because of (4) the design of the space and (5) the perceived technical skillset of the students there. Notably, non-dominant students face a multitude of (6) barriers corresponding with their social identities. We conclude with recommendations relevant to educators, makerspace administrators, and engineering leadership for alleviating barriers and supporting students' involvement in STEM makerspaces.